Implementation of Pay for Performance in the Public Sector in Indonesia - Vidya Imanuari Pertiwi; Revienda Anita Fitrie (Indonesian Association for Public Administration (IAPA), 2019)
Based on several studies on pay for performance (P4P) in Indonesia, we assess that it still needs a comprehensive understanding of how the implementation and the consequences arising from the implementation of P4P in Indonesia. Thus, this article aims to discuss the extent to which the implementation of P4P-based payroll systems in Indonesia and the consequences that will result. The methodology used is literature review, with outlined techniques from Wolfswinkel, Furtmueller, and Wilderom (2011). The results obtained that the Indonesian payroll design adheres to the pattern of single salary consisting of elements of the position (salary) and benefits (performance and expensiveness). Pay for performance is reflected in performance allowances. Performance allowances are given according to performance achievements for additional income and service motivation. Performance is obtained from presence-based assessments, employee work targets (SKP), and e-lapkin (Electronic Performance Report). The consequence of pay for performance is that there are gaps between Ministries, Institutions, Regions and Agencies in providing performance allowances, also the significance of improvements in public services has not yet been seen, especially the direct benefits to the public. The limitation is the lack of a comprehensive framework so that it is felt necessary to present research directly, so as to produce research that is closer to the actual conditions.